AN ANALYSIS OF CHILD LANGUAGE DEVELOPMENT - Okti Wilymafidini (Politeknik Negeri Bengkalis, 2018)
This research aims at explaining the description of child language development to show the capability of a child in producing and comprehending language. This is a descriptive research in which the writer describes all the data like what it is. Next, for presenting the data, the writer used the written form in order to give more explanation to the reader. From the data conducted it shows that Children utter their first word when they are around one year old; Three years old child is able to produce around 950 words; 95% of the words said by three years old child is clear; Three years old child is able to use prepositions correctly; He also understands simple questions, can identify color and counts items; The dominant case of language when a child is around three years old is unclear and unfamiliar words.